The effects of amplitude modulated transcranial alternating current stimulation on working memory of college students - Wang, Heng; Chen, Yan; Zhou, Ziyu; Jiang, Rui; Hu, Haowei; Zhao, Yan; Dimyati, K.; Tong, Shen; Wang, Ji; Zhang, Xiao (Frontiers in Human Neuroscience, 2025)
BackgroundRecent studies suggest that amplitude-modulated transcranial alternating current stimulation (AM-tACS) may enhance cognitive functions, but its mechanisms and optimal application remain unclear.MethodsThirty-three healthy university students were randomly assigned to Sham, tACS (40 Hz, 1 mA, bilateral prefrontal cortex), or AM-tACS (200 Hz carrier frequency) groups, in AM-tACS, the baseband modulation frequency was individualized based on the pre-task phase-locking value (PLV) derived from occipitofrontal EEG. Working memory (WM) was assessed via a delayed-match-to-sample task (accuracy and sensitivity index d’).ResultsCompared to Sham, the tACS group showed significant WM accuracy improvement (p < 0.05). AM-tACS exhibited a smaller but statistically significant enhancement in d’ (p < 0.05). EEG analysis revealed no PLV increase between stimulated regions, but a trend toward heightened frontal-occipital functional connectivity.ConclusionAmplitude-modulated transcranial alternating current stimulation effectively enhances WM in college students, though physiological mechanisms require further investigation with multimodal approaches. The compatibility of AM-tACS with real-time EEG monitoring highlights its potential for closed-loop neuromodulation systems, where stimulation parameters could be dynamically adjusted based on neural feedback.